Pigeon Rotavirus A as the cause of systemic infection in juvenile pigeons (young pigeon disease) - Meßmer, Christian; Rubbenstroth, Dennis; Mohr, Lydia; Peus, Elisabeth; Schreiber, Tim; Rautenschlein, Silke (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2022)
Recent investigations suggested pigeon associated Rotavirus Typ A genotype G18P[17] (RVA) as a causative agent of the classical ‘young pigeon disease’ (YPD). YPD was first described in the late 1980 s as an acute, mainly seasonally recurring disorder of mostly juvenile domestic pigeons (Columba livia) with clinical signs such as anorexia, dairrhea, vomiting, congested crops, weight loss and occasionally mortality. Various studies in the past indicated a multifactorial nature of YPD. Several pathogens, such as pigeon circovirus 1, avian adenoviruses and Escherichia coli were also suggested, but none of these could reproduce the disease experimentally. However, the impact of other pathogens on the clinical development of YPD cannot be excluded and requires further investigation. This present review summarizes available information on RVA-induced disease in pigeons, its association with YPD, the transmission, and diagnosis of the infection, and on prophylactic strategies to prevent RVA outbreaks.
Keywords: Pigeon-type Rotavirus A; young pigeon disease; mortality; transmission; vaccines; lineages